If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = x + 16 Reorder the terms: -7 = 16 + x Solving -7 = 16 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + -1x = 16 + x + -1x Combine like terms: x + -1x = 0 -7 + -1x = 16 + 0 -7 + -1x = 16 Add '7' to each side of the equation. -7 + 7 + -1x = 16 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 16 + 7 -1x = 16 + 7 Combine like terms: 16 + 7 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23
| 10x+4-22x=1-10x-9 | | -4(2x-3)=3+8x-12 | | 2/3+4/9= | | 1.5q-3.4-1.9q=-1.4q-4.8 | | 2x=3x+58 | | 14x+14(5)=27 | | 8-2(y+1)=-3y+1 | | x^3+x^2-46x+80=0 | | 8s^2-56s+80=0 | | 9x+7=3x-5 | | 14x*16=828727284 | | 5x-15y=30 | | -8+3=-9y+8 | | 14x*16= | | 68=34+34 | | 7x-19x=108 | | 68=34+ | | 68=34 | | 15+z=-4 | | 9xy-4x-3x-5xy= | | 34=23/34*3 | | x^6-12x^2+16=0 | | 2b^2+11b+5=0 | | 8(4k-4k)=-5k-32 | | -30=-9x | | 2(7x+9)+17-23(111)=1 | | 3x+2=5x-2 | | 1.33x=.25 | | 22-0.5Y=x | | 33x+4x=6 | | x=22+-0.5y | | x=22+-.5y |